Effect of bacterial amylase pretreatment on alcohol production from starch-based solid waste. Issue 5 (2nd September 2016) - Kumar, Vinod; Nanda, Manisha; Singh, Ajay
ABSTRACT: A number of different pretreatments involving biological, chemical, physical, and thermal approaches have been investigated over the years to reduce the cost of biofuel production. This study investigates the effect of bacterial amylase pretreatment on bioethanol production from different kinds of starch-based solid waste. We have isolated one strain ( Xenorhabdus japonica ) of amylase-producing bacteria from municipal waste dumping site's soil. Maximum ethanol yield was obtained after bacterial amylase pretreatment from wheat bread and rice (132 g/L), while the minimum was obtained from potato (99 g/L). Bacterial amylase pretreatment shows the best results as compared to the acid pretreatment.